Enhancing the education of paediatric nurses: A positive step towards achieving sustainable development goals - Aimable Nkurunziza; Godfrey Katende; Philomene Uwimana; Patricia J. Moreland; William E. Rosa; Marie Louise Umwangange; Dieudonne Kayiranga; Joselyne Rugema; Madeleine Mukeshimana (Nursing Open, 2023)
Abstract Aim The aim of this discursive paper was to describe and expound on how paediatric nurses will be able to address the needs of children and adolescents through the lens of selected Sustainable Development Goals (SDGs) in Rwanda. Design A discursive analysis of SDGs relating to the roles of paediatric nurses in the context of Rwanda. Methods A discursive method using SDGs as a guiding framework is used in this paper. We drew on our own experiences and supported them with the available literature. Results A collection of contextually relevant examples of how paediatric nurses will be able to address the needs of children and adolescents through the lens of selected SDGs in Rwanda was discussed. The selected SDGs expounded on were: no poverty, good health and well‐being, quality of education, decent work and economic growth, reduced inequalities, and partnerships for the goals. Conclusions There is no doubt that the paediatric nurses in Rwanda play undeniable key roles in attaining SDGs and their targets. Thus, there is a need to train more paediatric nurses with the support of the interdisciplinary partners. Collaboratively, this is possible in the bid to ensure equitable and accessible care to the current and future generations. Public contribution This discursive paper is intended to inform the different stakeholders in nursing practice, research, education and policy to support and invest in the advanced education of paediatric nurses for attainment of the SDGs.